An Analysis of the Grammatical Errors in the Narrative Writing of the First Grade Students of SMA 6 Yogyakarta - Hendriwanto Hendriwanto; Bambang Sugeng (JOURNAL OF EDUCATION, 2013)
This study was aimed at finding  out: (1) the types of grammatical errors in the narrative writing of the first grade students of SMA 6 Yogyakarta, and (2) the causes of the grammatical errors in their narrative writing. The study was a case study. The participants were 30 students of the first  grade students of Senior High School Six Yogyakarta in the academic year of 201112012.  The study comprised five  steps, namely collection of data, identification of errors, quantification of errors, description of errors, and explanation of errors. The research instrument was in the form  of a writing assignment. The data were obtained from  the students' writing works. The results of the study were as follows.  First, fourteen  types of the grammatical errors of the students'  narrative writing were found concerning  verb tenses, finite  verbs,  non-finite verbs, pronouns,  prepositions,  spelling, agreement of singular and plural, punctuation,  contexts of usage, contexts of meaning, redundancy, word choices, word orders, and unintelligibility. Second, the verb tense errors occupied the first  rank (24.47%), followed  by the pronoun errors (11.56%),  and the finite verb errors (10.51%).   Third, five  types of the causes of errors were: (1)  interference in copulative verbs, word orders, verb tenses, and article usages; (2) ignorance of rule restrictions in articles, relative clauses, causative verbs, and verb + gerund constructions; (3) incomplete application of rules in prepositions, verb phrases, subjects of the sentence, and objects of the sentence; (4) false  concepts hypothesized in past verb tenses, non-finite verbs,  agreement  of  the  singular  and plural,  and  adverbs  of  degree;  and (5)  over generalization in irregular past verbs, articles, verb phrases, and plural nouns.